"He said Ireland has more than one story": multiple belongings in perspective - Casal, Maria Teresa Correia,1964- (2011)
Focusing on non-fictional and fictional memoirs, respectively Hugo Hamilton's The Speckled People (2003), and Jennifer Johnston's The Gingerbread Woman (2000), this paper addresses the experience of those who find themselves perceiving the world from outside the walls of the Palace of Sans Souci, and who has a result try to work out how their perception may both belong to, and change, the prevailing picture of the world they inhabit.